THE IMPLEMENTATION OF THE DEEP LEARNING APPROACH BASED ON MINDFUL, MEANINGFUL, AND JOYFUL LEARNING IN HISTORY LEARNING AT SMA PGRI 1 PALEMBANG: IMPLEMENTASI PENDEKATAN DEEP LEARNING BERBASIS MINDFUL, MEANINGFUL, DAN JOYFUL LEARNING DALAM PEMEBLAJARAN SEJARAH DI SMA PGRI 1 PALEMBANG - Bagas Asmara; Sukardi; Nur Syafarudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study was motivated by the importance of instilling nationalism values in students amid the rapid development of globalization. History learning plays a significant role in shaping character, national identity, and patriotism. The study aimed to identify the forms and implementation of nationalism values in history learning at SMA Pembina Palembang.This research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation.The findings revealed that the implementation of nationalism values was carried out through both school activities and history learning in the classroom, including flag ceremonies, national commemorations, religious activities, and extracurricular programs. In history learning, nationalism values were integrated into topics related to the national struggle, unity, patriotism, and appreciation of national heroes. The implementation was supported by habituation, teacher role modeling, interactive learning methods, and the use of learning media. Supporting factors included the support of school principals, teachers, students, and school facilities, while limited resources remained an obstacle to the optimal implementation of several programs.The study concludes that the implementation of nationalism values in history learning at SMA Pembina Palembang has been carried out effectively and contributes to fostering patriotism, unity, responsibility, and national awareness among students